Optimization of an ammonia-cooled rectangular microchannel heat sink using genetic algorithm [electronic resource] - Ahmed Mohammed Adham, 1979-; Normah Mohd. Ghazali, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2013